ANALYSIS OF CAPITAL EXPENDITURE EFFECT FOR FINANCIAL PERFORMANCE OF MINERAL MINING COMPANY LISTED IN INDONESIA STOCK EXCHANGE (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
The purpose of this study are to measure on how effective the capital expenditure influence to financial performance in profitability aspect, to know the influence of capital expenditure on total asset turn over and to know on how the ability of company on debt payment which is pay at the time. This study used multiple regression model in which the data was obtained in the period 2010 to 2018 then derived into Q1 until Q4 for each year. In analyzing data, Ln Sales & Ln Asset becoming variable control in multiple regression model. The result in this study shows that capital expenditure is not significant effect on return on asset, total asset turns over, and coverage. It can be there are another variable that significant influence on all parameter on company performances. The results of this research indicate that mining company must maximize its assets to produce positive performance and the high value of capital expenditure does not guarantee it can produce positive contributions in the short term.